Second Primary Malignancies in Patients With Melanoma Subtypes: Analysis of 120,299 Patients From the SEER Database (2000-2016) - Loya, Asad; Gombos, Dan S.; Patel, Sapna P. (Frontiers in Oncology, 2022)
Purpose: Evaluate incidence of second primary malignancies (SPM) after non-acral cutaneous melanoma (NACM), acral lentiginous melanoma (ALM), mucosal melanoma (MM), and uveal melanoma (UM). Patients and Methods: First primary NACM, ALM, MM, and UM cases diagnosed 2000-2016 were extracted from SEER. Seer*Stat was used to calculate excess absolute risks (EAR) and standardized incidence ratios (SIR) of SPMs relative to a matched cohort from the general population. P-value of 0.05 determined significance. Results: Inclusion criteria was met by 109,385 patients with NACM, 2166 with ALM, 2498 with MM, and 6250 with UM. Increased incidence of malignancies occurred after NACM (SIR 1.51; 95%CI, 1.49-1.54), ALM (SIR 1.59; 95%CI, 1.40-1.81), MM (SIR 2.14; 95%CI, 1.85-2.45), and UM (SIR 1.24; 95%CI, 1.14-1.34) relative to the general population. Cutaneous melanoma occurred more frequently after NACM (SIR 9.54; 95%CI, 9.27-9.83), ALM (SIR 12.19; 95%CI, 9.70-15.14), MM (SIR 10.05; 95%CI, 7.18-13.68), and UM (SIR 2.91; 95%CI, 2.27-3.66). Patients with initial NACM (SIR 2.44; 95%CI, 1.64-3.51) and UM (SIR 44.34; 95%CI, 29.91-63.29) demonstrated increased incidence of eye and orbit melanoma. Renal malignancies occurred more frequently after NACM (SIR 1.24; 95%CI, 1.11-1.38), MM (SIR 3.54; 95%CI, 1.62-6.72) and UM (SIR 1.68; 95%CI, 1.09-2.48). Increased incidence of thyroid malignancies was observed after NACM (SIR 1.83; 95%CI, 1.61-2.06), ALM (SIR 3.74; 95%CI, 1.71-7.11), MM (SIR 4.40; 95%CI, 1.77-9.06), and UM (SIR 3.79; 95%CI, 2.52-5.47). Increased incidence of lymphoma was observed after NACM (SIR 1.20; 95%CI, 1.09-1.31) and ALM (SIR 2.06; 95%CI, 1.13-3.46). Conclusion: Patients with NACM, ALM, MM, and UM have increased incidence of SPMs compared to that expected from the general population. Each of these melanoma subtypes had increased occurrence of cutaneous melanoma and thyroid cancer; some, but not all, had increased occurrence of renal malignancies, eye and orbit melanoma, and lymphoma.